New insights into informal migrant employment: Hand car washes in a mid-sized English city. (August 2019) - Clark, Ian; Colling, Trevor
This article provides new analytical insight into migrant labour by examining a newly emergent low-margin sector, hand car washes (HCWs). The sector is co-created by pressures from above in the form of economic restructuring and from below by employers and migrants who diffuse fluid and flexible low-wage employment. The diffusion of HCWs demonstrates how exploitative privatized employment generates autonomous economic growth in the unregulated economy. The formal and informal economies are however interlinked and overlapping within and beyond the labour process. Locally, HCWs have the potential to become the established car wash sector, putting regulated outlets in a state of uncertainty as informalization in employment if not business practice becomes the norm.